The ghostly mystery - Adler, David A.; Natti, Susanna (New York : Puffin Books, 2005)
Cam uses her photographic memory to catch a thief disguised as a ghost.
Keywords: Robbers and outlaws -- Fiction; Ghosts -- Fiction; Mystery and detective stories